Alcohol use and unprotected sex among HIV-infected Ugandan adults: Findings from an event-level study - Woolf-King, Sarah E.; Fatch, Robin; Cheng, Debbie M.; Muyindike, Winnie; Ngabirano, Christine; Kekibiina, Allen; Emenyonu, Nneka; Hahn, Judith A. (Archives of sexual behavior, 2018)
While alcohol is a known risk factor for HIV infection in sub-Saharan Africa (SSA), studies designed to investigate the temporal relationship between alcohol use and unprotected sex are lacking. The purpose of this study was to determine if alcohol used at the time of a sexual event is associated with unprotected sex at that same event. Data for this study were collected as part of two longitudinal studies of HIV-infected Ugandan adults. A structured questionnaire was administered at regularly scheduled cohort study visits in order to assess the circumstances (e.g., alcohol use, partner-type) of the Most Recent Sexual Event (MRSE). Generalized estimating equation (GEE) logistic regression models were used to examine the association between alcohol use (by the participant, the sexual partner, or both the participant and the partner) and the odds of unprotected sex at the sexual event while controlling for participant gender, age, months since HIV diagnosis, unhealthy alcohol use in the prior 3 months, partner-type, and HIV status of partner. A total of 627 sexually active participants (57% women) reported 1,817 sexual events. Of these events, 19% involved alcohol use and 53% were unprotected. Alcohol use by one’s sexual partner (aOR) = 1.70; 95%CI = 1.14, 2.54) or by both partners (aOR: 1.78; 95%CI: 1.07, 2.98), during the MRSE significantly increased the odds of unprotected sex at that same event. These results add to the growing event-level literature in SSA and support a temporal association between alcohol used prior to a sexual event, and subsequent unprotected sex.
Keywords: HIV; Condom; Alcohol; Sex event